Corporate Social Responsibility and labor relations: a research agenda about internal stakeholders management in un's global compact signatory corporations - Patrus, Roberto; Carvalho Neto, Antônio Moreira de; Coelho, Helena Maria Queiroz; Teodósio, Armindo dos Santos de Sousa (Review of Business Management, 2013)
Literature often presents the concept of Corporate Social Responsibility (CSR) in association with the idea of Business Ethics. In this article, we saw the need to ellaborate a theoretical model of Business Ethics that was capable of guiding research on Corporate Social Responsibility practices aimed at organizations’ internal public. To this end, we analyzed different Business Ethics fields – namely Responsibility Ethics, ethics that reaffirm the principle of humanity and ethics that generate conventional morality, so as to avoid automatic associations with the idea of Corporate Social Responsibility. The theoretical dialogue of these two major constructs (Business Ethics and CSR) with the field of Labor Relations is dealt with in accordance with these three dimensions of ethics. To find out how a company that desires to be socially responsible relates to its employees, there are indicators that are strongly related to key aspects of labor relations, as shown by the UN’s Global Compact Agenda. This interface produced the methodological guidelines that conducted research data collection and analysis, pointing out important challenges in this agenda, as well as serving as a basis for further studies in this field.